2016
DOI: 10.1097/jom.0000000000000741
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Are Associated With Occupational Health Office Staffing, Job Stress, and Job Satisfaction?

Abstract: Offices that required a provider presence had roughly one provider, seven nurses, and three clerical staff per 8000 personnel served. Occupational health workers are generally highly satisfied, and staffing has little relation to sources of job stress and satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Work stress in healthcare industry has been a long-standing concern [37]. This finding revealed that CHNs in Southwestern China experienced moderate stress.…”
Section: Discussionmentioning
confidence: 92%
“…Work stress in healthcare industry has been a long-standing concern [37]. This finding revealed that CHNs in Southwestern China experienced moderate stress.…”
Section: Discussionmentioning
confidence: 92%
“…For example, SARS-CoV-2 sample collections, laboratory processing, contact tracing, and the telephone call center were labor intensive, and staffing fluctuated over time. Published human resource guides for medical setting staff-to-patient ratios and human resource calculators reference non-pandemic practice needs and thus do not necessarily speak to the current situation 1 , 10 . The call center handled thousands of telephone calls, the testing operations collected and processed more than 2000 nasopharyngeal swab samples some weeks, and thousands of contact tracing telephone interviews were performed.…”
Section: The Workplace Occupational Health Clinic and Management Supportmentioning
confidence: 99%
“…Published human resource guides for medical setting staff-to-patient ratios and human resource calculators reference non-pandemic practice needs and thus do not necessarily speak to the current situation. 1,10 The call center handled thousands of telephone calls, the testing operations collected and processed more than 2000 nasopharyngeal swab samples some weeks, and thousands of contact tracing telephone interviews were performed. Clinic staffing expanded as the volume and range of interventions increased.…”
Section: The Workplace Occupational Health Clinic and Management Supportmentioning
confidence: 99%
See 1 more Smart Citation